Highlighting the biological potential of the brown seaweed Fucus spiralis for skin applications - Freitas, Rafaela (2020)
Skin aging is a biological process influenced by intrinsic and extrinsic factors. The last ones, mainly exposure to UV radiation, increases reactive oxygen species (ROS) production leading to a loss of extracellular matrix, also enhanced by enzymatic degradation of matrix supporting molecules. Thus, and with the growing demand for eco-friendly skin products, natural compounds extracted from brown seaweeds revealed to be good candidates due to their broad range of bioactivities, especially as antioxidants. The aim of this study was to assess the dermo-cosmetic potential of di erent fractions obtained from the brown seaweed Fucus spiralis. For this purpose, in vitro antioxidant (Total Phenolic Content (TPC), 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, Ferric Reducing Antioxidant Power (FRAP), Oxygen Radical Absorbance Capacity (ORAC)), anti-enzymatic (collagenase, elastase and hyaluronidase), antimicrobial, anti-inflammatory (NO production) and photoprotective (ROS production) capacities were evaluated. Although nearly all fractions evidenced antioxidant e ects, fraction F10 demonstrated the highest antioxidant ability (EC50 of 38.5 g/mL, DPPH assay), and exhibited a strong e ect as an inhibitor of collagenase (0.037 g/mL) and elastase (3.0 g/mL). Moreover, this fraction was also the most potent on reducing ROS production promoted by H2O2 (IC50 of 41.3 g/mL) and by UVB (IC50 of 31.3 g/mL). These bioactivities can be attributed to its high content of phlorotannins, as evaluated by LC-MS analysis, reinforcing the potential of F. spiralis for further dermatological applications.